Clinical Pharmacology Of Metabolism-Activating And Correcting Drugs (Texas Journal of Medical Science, 2025)
The article covers the issues of drug metabolism in patients with various liver diseases, presents pathophysiological mechanisms of impaired biotransformation of substances depending on the severity of hepatocyte damage, names the causes of drug interactions of pharmacological agents, leading to an undesirable increase in the concentration of the drug in the blood, strengthening and prolongation of the therapeutic effect with an increased risk of side effects